The efficacy of cervical encerclage on the course of labour in well selected cases: a prospective study at a tertiary care hospital - Shinde, Kunaal; Karake, Anand V.; Shekhawat, Gulabsingh; Shivale, Hiralal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The two major problems for modern obstetrics and perinatal medicine are recurrent second trimester abortions and preterm delivery. Cervical insufficiency or incompetency is defined as the inability of the uterine cervix to retain a pregnancy in the absence of contractions or labor. Cervical encerclage is a simple but a resourceful procedure for improving the fetal outcome in cases proven with cervical incompetence, is a boon to modern obstetrics. Methods: A prospective analytical study was carried out at tertiary care teaching hospital for a period of ten years. Three hundred and twenty cases of bad obstetric history (repeated abortions, preterm labor) with previous pregnancy losses probably due to cervical incompetence or ultrasonographical evidence of short cervix were included in the study. These cases were subjected to cervical encerclage operation in the second trimester. Results: Out of the 289 cases, who underwent McDonald’s procedure, 12 women had abortion, 66 had preterm labor and 211 women reached term. Out of the 31 cases who underwent Wurm’s procedure; 4 had abortion, 17 had preterm delivery and 10 women reached to term. In the present study, the average interval from cerclage to delivery was 115 days. It was observed that the fetal salvage rate was unsatisfactory in women having short cervix with open internal os before encirclage. Infant salvage rate in this study after encerclage operation was 86%. Conclusions: Cervical encerclage when done in properly selected cases, results in improvement in fetal salvage up to eighty percent.